(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the job orientation of medical students at Dai Nam University in 2025. Subjects and Methods: A cross-sectional study was conducted on 360 General Medicine students at Dai Nam University. Data were collected through an online self-administered questionnaire. Results: The study showed that 88.1% of students had a job orientation, of which 41.4% had a clear plan, 46.7% were unclear, and 11.9% had no orientation. Surgery was the most chosen specialty (20%), followed by Pediatrics (12.5%), Obstetrics (11.4%), Dermatology (11.4%), and Internal Medicine (10%). Regarding post-graduation plans, 41.4% chose to undertake practical training to obtain a medical practice license, 21.1% planned to take the residency exam, and 20.5% intended to pursue postgraduate studies. More than half of the students preferred working in the public healthcare sector (50.3%), 27.2% chose the private sector, and only 0.8% intended to work for non-governmental organizations. Regarding the workplace location, 50% of students preferred to work in centrally governed cities. The most important factor influencing workplace selection was working conditions (39.44%), followed by promotion opportunities (23.33%) and salary (19.17%). Conclusion: Medical students at Dai Nam University have relatively clear career orientations, mostly choosing common clinical specialties and showing a preference for working in public healthcare systems in major cities. The findings provide a basis for the university to strengthen career counseling and support for students.